Analyzing voice in language policy documents of the Moroccan government - Monera Almohawes (Cogent Arts & Humanities)
This paper examined the different voices present in language policy documents in article 5 which is the section devoted to language in the Moroccan constitution of 2011 using critical discourse analysis based on three levels of language policy analysis: discourse, contextual, and textual analyses. It showed how these documents reflect the ideological interests of policymakers in Moroccan society. These levels are the analyses of co-text in article 5 of the constitution; its relationship with other texts (intertextuality); concrete situations, such as language policy in general and that in Morocco in particular. The analysis showed that there are many different voices in language articles of the Moroccan constitution, but two are the most prominent: one based on national identity and values and the other grounded in liberty and language rights. These two prominent ones based on multilingualism and linguistic pluralism and focusing on Moroccan identity, history, and unity as one nation. The former is supported by the inclusion of a new indigenous language as an official language of the country and respect for its culture and people. The latter tends to denote that despite the addition of another official language, the country remains one unified nation, and Arabic is still saved and protected by the language policy stipulated in the new constitution.